Southwest Research-Extension Center, Field Day 2010 (Kansas Agricultural Experiment Station Research Reports, 2010)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: crops; tillage; soil fertility; irrigation; insect control; weed science; SRP1034; 2010